2002
DOI: 10.1159/000047824
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human Somatostatin Receptor 2 Promotes Apoptosis Through a Mechanism that is Independent from Induction of p53

Abstract: The ability of both somatostatin (SS) and its stable analogues to inhibit cell growth depends on the stimulation of specific membrane receptors (SSTR1-5), which belong to the G protein-coupled receptor family. Accumulating evidence suggests that the SSTR2 plays a major role in mediating cell cycle arrest, and it is also clear that SHP-1, a cytoplasmic phosphotyrosine phosphatase (PTP), is an essential component of the SSTR2-mediated cytostatic effect. In contrast, the possibility that SSTR2 activation may also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 30 publications
2
40
0
5
Order By: Relevance
“…Similar results have been demonstrated in different cancer cells [17]. Although controversial observations on the influence of SSTR2 activation on the p53 induced apoptosis have been reported, the findings in this study showed that the cellular level of p53 was significantly increased in SSTR2 transfected tumors [18,19]. The differences in p53 accumulation upon SSTR2 activation could be consequences of the different experimental cancer cells used in these studies.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results have been demonstrated in different cancer cells [17]. Although controversial observations on the influence of SSTR2 activation on the p53 induced apoptosis have been reported, the findings in this study showed that the cellular level of p53 was significantly increased in SSTR2 transfected tumors [18,19]. The differences in p53 accumulation upon SSTR2 activation could be consequences of the different experimental cancer cells used in these studies.…”
Section: Discussionsupporting
confidence: 88%
“…This result is consistent with our previous published data, demonstrating that sst2 expression also triggers apoptosis in the human pancreatic cancer BxPC-3 cells, 10 and with the demonstration of a somatostatin-mediated apoptotic action in the myeloïd cancer HL-60 cells, which only express the subtype 2 of somatostatin receptor. 3 Beside its apoptotic action on cancer cells, somatostatin has also been shown to decrease cell survival in several non-cancer cell models, including intestinal epithelial cells, 4 fibroblasts from Graves' ophtalmopathy 6 and peripheral blood lymphocytes. [7][8][9] However, mechanisms for somatostatin-induced apoptosis and receptor subtype implication were not described in these models.…”
Section: Discussionmentioning
confidence: 99%
“…2 Whereas somatostatin effect on cell cycle arrest has been extensively studied, mechanisms for somatostatin-induced apoptosis and receptor subtype implication are only partially elucidated. Somatostatin has been shown to induce cell death in both normal and tumoral cell models [3][4][5][6][7][8][9] . Among the five somatostatin receptors, sst3 and sst2 have been found to play a critical role in somatostatin-induced apoptosis of normal and tumor cells, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When sst3 is A c c e p t e d M a n u s c r i p t 10 transfected into previously sst-free cell lines, the addition of octreotide causes the upregulation of the tumor suppressor protein p53, which is associated with a dephosphorylation-dependent conformational change of p53 as well as induction of Bax (Sharma, Srikant 1998). Sst2 induces apoptosis in a SHP-1-dependent manner by a mechanism independent of p53 (Teijeiro et al, 2002). Recently, a novel mechanism involved in the apoptotic effect of sst2 has been identified.…”
Section: -Inhibition Of Cell Invasion By Somatostatinmentioning
confidence: 99%